2020
DOI: 10.1002/cti2.1196
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between serum complement component C1q levels and whole blood type‐1 interferon signature in active tuberculosis and QuantiFERON‐positive uveitis: implications for diagnosis

Abstract: Objectives. To examine the relation between serum C1q levels and blood type-1 interferon signature (type-1 IFN signature) in active pulmonary tuberculosis (APTB) and to determine whether combined measurement of serum C1q and type-1 IFN signature may add to the diagnosis of QuantiFERON-positive (QFT +) patients with uveitis of unknown cause. Methods. C1q was determined (ELISA) in serum from two distinct Indonesian cohorts, and in total, APTB (n = 72), QFT + uveitis of unknown aetiology (n = 58), QFT À uveitis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…C1q protein levels in serum are increased in individuals with TB disease and not in the most common confounder diagnoses, including other mycobacterial infections and respiratory diseases 16 . These data have been confirmed in other cohorts focusing on TB and uveitis 17 . In experimental infection models increased serum C1q coincided with classical hallmarks of progressive disease 18 .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…C1q protein levels in serum are increased in individuals with TB disease and not in the most common confounder diagnoses, including other mycobacterial infections and respiratory diseases 16 . These data have been confirmed in other cohorts focusing on TB and uveitis 17 . In experimental infection models increased serum C1q coincided with classical hallmarks of progressive disease 18 .…”
Section: Introductionsupporting
confidence: 76%
“…C1q levels in serum and culture supernatants were analyzed by ELISA, as described previously 17 . Briefly, Maxisorp plates (Nunc) were coated with mouse anti-human C1q mAb 2204 (Nephrology, LUMC) in coating buffer (0.1 M NA2CO3, 0.1 M NaHCO3, pH 9.6) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…An additional mechanism by which AMI could influence the host response against Mtb is through Ab-mediated complement engagement and deposition ( 182 – 184 ). As discussed previously, transcripts of different complement genes were strongly increased during active TB-disease, which were considered important biomarker candidates ( 18 , 20 , 23 26 ). In addition, increased concentrations of circulating immune complexes were detected in serum of patients with subclinical and clinical ATB ( 24 ), however, the antigen in these complexes remains unknown.…”
Section: The Mechanistic Role Of Abs In Tbmentioning
confidence: 67%
“…Furthermore, in many transcriptomic studies also components of the complement pathway were identified, predominantly transcript-markers from the classical pathway, that were differentially expressed in the blood of ATB compared to LTBI: in particular Complement component1qB ( C1QB) and C1QC were higher expressed, and in support of this, serum C1q-protein was found to be a diagnostic biomarker for ATB ( 18 , 20 , 23 25 ). More recently, it was reported that the combined measurement of serum C1q and whole blood type-1 interferon (IFN) signature might help improving the diagnosis of ATB ( 26 ). Together, these studies hint to the potential influence of humoral immune components in TB, including innate and possibly also adaptive humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Schrijver et al further evaluated that the peripheral blood type 1 IFN gene signature score displayed an inverse correlation with serum complement component C1q. Combined measurement resulted in improved identification of ocular TB from uveitis with coincidental QFT positivity yet without other signs of active TB infection especially in high TB-endemic regions 121 . In addition to multiple studies showing an important role of IFN signaling in the pathogenesis of pulmonary TB 122 , 123 an in vitro study also displayed strong IFN signaling in RPE cells after Mtb infection 124 .…”
Section: Novel Biomarkers For Diagnosis Treatment Effectiveness and P...mentioning
confidence: 99%